1979
DOI: 10.1001/archderm.115.7.840
|View full text |Cite
|
Sign up to set email alerts
|

Tar gel-phototherapy for psoriasis. Combined therapy with suberythemogenic doses of fluorescent sunlamp ultraviolet radiation

Abstract: To determine the efficacy of suberythemogenic ultraviolet phototherapy in conjunction with administration of a tar gel (SEUV TG), patients with widespread psoriasis were treated by application of a tar gel preparation followed after 12 hours by suberythemogenic doses of fluorescent sunlamp irradiation. In paired comparison studies, therapeutic effects of the following treatments were evaluated: SEUV-TG, a more conventional erythemogenic tar gel phototherapy regimen (modified Goeckerman), the tar gel alone, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…According to him, tar is a photosensitizer which when combined with UVB light produces efficacy greater than either treatment alone. Further studies have confirmed that tar plus UVB is more effective than either therapy alone [79]. This is also supported by our study, since many of our patients had used phototherapy in the past (57.1%) with inadequate results.…”
Section: Discussionsupporting
confidence: 86%
“…According to him, tar is a photosensitizer which when combined with UVB light produces efficacy greater than either treatment alone. Further studies have confirmed that tar plus UVB is more effective than either therapy alone [79]. This is also supported by our study, since many of our patients had used phototherapy in the past (57.1%) with inadequate results.…”
Section: Discussionsupporting
confidence: 86%
“…All of the above‐mentioned studies in this section were assigned a grade of evidence of B, resulting in an overall level of evidence of 3 due to conflicting results. For further studies on phototherapy included by the systematic literature search 258–264 see the online evidence tables.…”
mentioning
confidence: 99%
“…A total of six studies met the criteria for inclusion in the guidelines. Only one study (grade C) examined coal tar monotherapy [145]. This results in an evidence level of 4.…”
Section: Topical Therapymentioning
confidence: 99%